1990
DOI: 10.1111/j.1528-1157.1990.tb05382.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Methylxanthines on the Anticonvulsant Action of Common Antiepileptic Drugs in Mice

Abstract: The protective activity of carbamazepine (CBZ, 60 min before testing), phenobarbital (PB, 120 min), phenytoin (PHT, 120 min), and valproate (VPA, 30 min) alone or concurrent with methylxanthine derivatives was evaluated against maximal electroshock-induced seizures (MES) in male mice. All drugs were administered intraperitoneally (i.p.), and the protection offered by antiepileptic drugs (AEDs) was expressed as ED50 in mg/kg. Caffeine sodium benzoate in doses of 0.0595-0.476 mmol/kg (11.55-92.4 mg/kg) distinctl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Further studies in the field of experimental epilepsy have also provided evidence that theophylline, diprophylline and enprofylline exhibit different effects on the protective efficacy of common antiepileptic drugs against convulsions induced in animals (Czuczwar et al 1987a(Czuczwar et al , b, 1990). In addition, other experimental studies showed a clear difference in the ECoG recordings and behavioural effects in rats pretreated with theophylline or enprofylline when the behavioural excitation was induced by subconvulsive doses of pentylenetetrazole (Cutrufo et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies in the field of experimental epilepsy have also provided evidence that theophylline, diprophylline and enprofylline exhibit different effects on the protective efficacy of common antiepileptic drugs against convulsions induced in animals (Czuczwar et al 1987a(Czuczwar et al , b, 1990). In addition, other experimental studies showed a clear difference in the ECoG recordings and behavioural effects in rats pretreated with theophylline or enprofylline when the behavioural excitation was induced by subconvulsive doses of pentylenetetrazole (Cutrufo et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the pure drug-resistant epilepsy, some epileptic patients may face intractable seizures due to other than pharmacoresistance reasons. During the 90s of the XX century, a number of experimental papers clearly indicated that caffeine, administered in doses far below its convulsive potential, significantly reduced the anticonvulsant activity of conventional antiepileptic drugs against maximal electroshock-induced seizures in mice [124][125][126]. It is noteworthy, that this untoward effect of caffeine did not undergo any tolerance and actually, was increased upon chronic administration of the methylxanthine derivative [125,126].…”
Section: Drug-resistant Epilepsymentioning
confidence: 94%
“…+, at least 25% increase in the respective ED50 value; ++, at least 50% increase; +++, at least 90% increase; 0, no significant effect. Data were transformed from Czuczwar et al[124].…”
mentioning
confidence: 99%
“…At high doses, caffeine and related methylxanthines have acute convulsive effects. Caffeine causes seizures in genetically susceptible rats (De Sarro et al., 1997) and reduces seizure thresholds to certain convulsants (Chu, 1981; Czuczwar et al., 1990). The mechanism may involve the antagonism of adenosine (adenosine promotes seizure termination) (Whitcomb et al., 1990).…”
mentioning
confidence: 99%